2022
DOI: 10.1128/spectrum.01951-21
|View full text |Cite
|
Sign up to set email alerts
|

Selective Metal Chelation by a Thiosemicarbazone Derivative Interferes with Mitochondrial Respiration and Ribosome Biogenesis in Candida albicans

Abstract: The increasing incidence of fungal infections and resistance to existing antifungals call for the development of broad-spectrum antifungals with novel mechanisms of action. In this study, we demonstrate that a thiosemicarbazone derivative 19ak selectively inhibits mitochondrial respiration mainly by retarding mitochondrial respiratory chain complex I activity through iron chelation and inhibits ribosome biogenesis mainly by disrupting intracellular zinc homeostasis in C. albicans .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…The mitochondria of C. albicans were isolated as previously described with some modifications ( 42 ). Briefly, C. albicans SC5314 cells were washed twice with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The mitochondria of C. albicans were isolated as previously described with some modifications ( 42 ). Briefly, C. albicans SC5314 cells were washed twice with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Impairment of zinc utilization results in the inhibition of C. albicans protein translation ( 23 , 24 ), which explains the significant inhibition of biofilm growth and pathogenicity following HAL-ES-mediated treatment in our previous research ( 5 ). Approximately 8% of yeast proteins require zinc for their activity ( 25 ), especially enzymes related to pathogen survival and virulence as well as zinc finger transcription factors involved in transcriptional regulation ( 22 , 24 ).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the uptake, storage, and utilization of zinc in C. albicans biofilms can be severely impaired by HAL-ES. A previous study found that simple zinc chelators only inhibited the growth of C. albicans , with concentrations well above the MIC required to produce a fungicidal effect ( 23 ). However, we found that the MIC and MFC were similar for HAL-ES because, compared to a zinc chelator, it caused an overall reduction in the uptake, storage, and utilization of zinc by C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…Ribosome biogenesis in eukaryotes is the basis of cell life and most cellular processes, including growth and cell division [51]. Some scholars have found that destroying the intracellular zinc homeostasis of C. albicans inhibits ribosome biogenesis in eukaryotes and then selectively inhibits mitochondrial respiration to prevent fungal contamination [52]. In eukaryotes, ribosome biogenesis involves producing and correctly assembling four rRNAs and approximately 80 ribosomal proteins [53].…”
Section: Discussionmentioning
confidence: 99%